Interannual variation in littoral benthic macroinvertebrate communities under contrasting crayfish predation in a large boreal lake - Nzobeuh, Polain (2014)
Long term studies are widely used nowadays in many fields of ecology. For instance, records over years represent a valuable tool to monitor and comprehend environmental changes. In freshwater ecology, long term studies are often applied in restoration effect assessments using a before-after-control-impact design. Little is known about the long term effects of freshwater predators on their prey, for example of how crayfish as omnivorous predators affect macroinvertebrate prey communities. Bottom substrate of stony littoral shores in three sites of Lake Päijänne, in Central Finland, were sampled for macroinvertebrates (MI) during five consecutive years and identified mainly to species. Of the three sites one was without crayfish, a second with a newly-introduced signal crayfish population, and a third one with a well-established signal crayfish population. Annual crayfish catching was also performed at the sites. Crayfish establishment was not yet successful as there was no population development after the introduction. Therefore, MI density and taxa richness showed no clear trend, though there were differences among years after the introduction of the predator. Snail densities and species richness increased one year after the introduction and later decreased significantly. No change was observed at the control site in density and taxa richness of MI and snails over years whereas at the crayfish site, there was a significant increase in total density and taxa richness in the last year. This might result from decreased crayfish abundance in the last two study years. Ordination analysis showed no clear interannual directional change in community composition, but the sites were clearly differentiated. The study showed that the effects of established signal crayfish populations on MI communities are fairly consistent in time, but that crayfish establishment and manifestation of effects on MI may require considerable time in large boreal lake littorals.